2015
DOI: 10.1152/ajplung.00011.2014
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of influenza A virus replication in human lung epithelial cells by noncytotoxic concentrations bafilomycin A1

Abstract: Subcellular trafficking within host cells plays a critical role in viral life cycles, including influenza A virus (IAV). Thus targeting relevant subcellular compartments holds promise for effective intervention to control the impact of influenza infection. Bafilomycin A1 (Baf-A1), when used at relative high concentrations (≥10 nM), inhibits vacuolar ATPase (V-ATPase) and reduces endosome acidification and lysosome number, thus inhibiting IAV replication but promoting host cell cytotoxicity. We tested the hypot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(54 citation statements)
references
References 61 publications
(76 reference statements)
1
53
0
Order By: Relevance
“…As expected, azithromycin monotherapy did not confer protection in terms of SR and weight loss; nevertheless, we interestingly observed that this macrolide could reduce viral replication in vivo and in vitro. These results are in agreement with previous studies where macrolides were associated with reduced viral titers in infected cells . Such direct antiviral effect was suggested to occur during the middle‐to‐late stage of the replication cycle .…”
Section: Discussionsupporting
confidence: 93%
“…As expected, azithromycin monotherapy did not confer protection in terms of SR and weight loss; nevertheless, we interestingly observed that this macrolide could reduce viral replication in vivo and in vitro. These results are in agreement with previous studies where macrolides were associated with reduced viral titers in infected cells . Such direct antiviral effect was suggested to occur during the middle‐to‐late stage of the replication cycle .…”
Section: Discussionsupporting
confidence: 93%
“…Four of the seven miRNAs, miR-143, miR-101, miR-30c and miR-26a, have been shown in previous studies to regulate insulin signalling and lipid metabolism and to be involved in diabetes [4346], and thus they may play important roles regulating changes in maternal metabolism occurring early during pregnancy. In addition, miR-26a and let-7f have been shown to regulate macrophage- and T-cell-mediated immunity [4750] which would be consistent with a role in establishing maternal immuno-tolerance, a key function during early pregnancy. Finally, miR-101, miR-205 and miR-26a are known regulators of angiogenesis [5154], a key process during development of foeto-placental and maternal tissues during pregnancy.…”
Section: Resultsmentioning
confidence: 84%
“…In both normal and malignant cells, autophagy may be induced in response to cellular stress, 62 including nutrient deprivation, hypoxia, and toxin accumulation 62 . The outcome of autophagy induction however, affects the cell in various ways, being protective, and promoting survival, or causing growth arrest and triggering programmed cell death 67 . The molecular components of this pathway were first discovered in yeasts and include more than 40 autophagy-related (ATG) proteins.…”
Section: General Aspects Of Autophagymentioning
confidence: 99%